2003
DOI: 10.1073/pnas.2233561100
|View full text |Cite
|
Sign up to set email alerts
|

Premature telomeric loss in rheumatoid arthritis is genetically determined and involves both myeloid and lymphoid cell lineages

Abstract: In rheumatoid arthritis, peripheral blood T cells have age-inappropriate telomeric erosion. We examined whether HLA-DRB1*04 alleles, the major susceptibility genes for this disease, confer risk for T cell senescence. In healthy individuals, HLA-DRB1*04 alleles were associated with excessive loss of telomeres in CD4 ؉ T cells. Accelerated telomeric erosion occurred during the first two decades of life and was followed by reduced homeostatic T cell proliferation during adulthood. Premature telomeric loss also af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
195
2
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 191 publications
(213 citation statements)
references
References 45 publications
10
195
2
4
Order By: Relevance
“…CD28 null T lymphocytes accumulate during aging and cancer presumably due to a prolonged exposure to common persistent antigens (Effros et al ., 2003; Effros, 2011). They are also found in young individuals as a result of chronic antigenic stimulation (Effros et al ., 2003; Effros, 2011) or chronic immune degenerative disorders such as juvenile idiopathic arthritis (Dvergsten et al ., 2013), myelodysplastic syndromes (Xiao et al ., 2013), idiopathic CD4 lymphopenia (Bignon et al ., 2015), or RA (Schönland et al ., 2003). The loss of CD28 is not only a result of T‐cell receptor (TCR) activation.…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…CD28 null T lymphocytes accumulate during aging and cancer presumably due to a prolonged exposure to common persistent antigens (Effros et al ., 2003; Effros, 2011). They are also found in young individuals as a result of chronic antigenic stimulation (Effros et al ., 2003; Effros, 2011) or chronic immune degenerative disorders such as juvenile idiopathic arthritis (Dvergsten et al ., 2013), myelodysplastic syndromes (Xiao et al ., 2013), idiopathic CD4 lymphopenia (Bignon et al ., 2015), or RA (Schönland et al ., 2003). The loss of CD28 is not only a result of T‐cell receptor (TCR) activation.…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…The requirements for continuous cell production are immense; adult humans need to produce 1.5 million blood cells every second (24). Studies examining granulocyte telomeres have shown that this enormous proliferative stress is even more pronounced in RA (25). Neutrophils from RA patients have telomere sequences that are shortened by Ͼ1,000 bp as compared with those from age-matched controls (25).…”
mentioning
confidence: 99%
“…CD4ϩ,CD28Ϫ T cells are end-differentiated with short telomeres and sluggish cell replication, identifying them as senescent cells (12,13). Besides loss of the costimulatory molecule CD28, they are functionally characterized by the de novo expression of a series of novel regulatory receptors (11,14,18).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the entire T cell population is abnormal. Specifically, CD4ϩ T cells from patients with RA display phenotypic and functional changes indicative of premature senescence (12,13). CD4ϩ T cells from patients with RA have shortened telomeres, suggesting an intense proliferative history.…”
mentioning
confidence: 99%